Detection of Cavitation States with Microphone Placed Outside Pipe Components - NAGAYA, Yukinori; MURASE, Michio (Journal of Environment and Engineering, 2012)
In this paper, we experimentally investigated detection of cavitation states using microphones placed outside a pipe at positions upstream and downstream from an orifice. From the visualization of cavitation bubbles and the characteristics of accelerometer outputs, the cavitation states from the orifice could be classified into 4 states; (A) no cavitation, (B) bubble collapse in the orifice, (C) bubble collapse at the center of the pipe and (D) bubble collapse near the pipe wall. The signal treatment technique for microphones was examined to improve detection sensitivity and the frequency characteristics were evaluated to detect a weak cavitation state. As the results, the ratios of (Leq-L50) (Leq: equivalent sound level, L50: 50 % percentile level) were selected to improve the detection sensitivity for the strong cavitation state (D). We proposed the evaluation of the power spectrum ratios (PSRs) between downstream and upstream from an orifice at each frequency band and their counts to detect the weak cavitation states (B) and (C). From the combination of the ratios of (Leq-L50), PSRs and their counts, the cavitation states (B), (C) and (D) were successfully detected and classified. Finally we discussed applicability of the proposed cavitation detection methods to components in plant piping systems.